Peter's School Day : A Peter Rabbit Tale - Potter, Beatrix, 1866-1943; Potter, Beatrix, 1866-1943.; Taylor, Eleanor, 1969- (New York : Frederick Warne, an imprint of Penguin Random House LLC, 2021)
Getting ready to start forest school with Benjamin Bunny, Peter gets apprehensive when he realizes his sisters wont be there until Mrs. Rabbit shows him that schools not so scary after all.
"The world of Peter Rabbit"--Page 4 of cover.
Keywords: Peter Rabbit -- (Fictitious character) -- Juvenile fiction; Peter Rabbit -- (Fictitious character) -- Fiction; Rabbits -- Juvenile fiction; First day of school -- Juvenile fiction; Rabbits -- Fiction; First day of school -- Fiction; Schools -- Fiction; Picture books; Picture books